Performance evaluation of ceramic pot filters combined with adsorption processes for the removal of heavy metals and phenolic compounds - Andrea Pérez-Vidal; Jorge Antonio Silva-Leal; Jaime Diaz-Gómez; Camilo J. Meneses-Torres; Juan E. Arias-Vallejo; Giovanna A. Giraldo-Tenorio; Maria Camila Bacca-Jordán (IWA Publishing, 2021)
It has been demonstrated that the ceramic pot filters (CPFs) with impregnated colloidal silver are efficient for the removal of turbidity and pathogens for household water treatment. This investigation evaluated the efficiency of two filter models for the removal of chemical contaminants (Hg, Pb, As and phenolic compounds) during 175 days. The first model is a traditional CPF impregnated with colloidal silver and the second consists of the ceramic silver-impregnated pot plus a post-filtration column with granular activated carbon and zeolite (CPF + GAC-Z). The results of the CPF showed average efficiencies of 91.5% (Hg), 92% (Pb), 50.2% (As) and 78.7% (phenols). The CPF + GAC-Z showed similar efficiencies for the removal of heavy metals (92.5% Hg, 98.1% Pb and 52.3% As) and a considerably higher efficiency for the removal of phenols (96.4%). The As concentration of the filtered water in both systems was higher than the regulatory limit. The ceramic pot was responsible for the highest removal of chemical compounds. It can be concluded that the traditional CPF is a viable option for water supply treatment at the household level for the removal of chemical contaminants. The efficiency of this filter can be improved with the post-filtration column mainly for the removal of organic constituents. HIGHLIGHTS The ceramic pot filter (CPF) is a viable household technology for chemical contaminants.; The combined use of the ceramic pot with granular activated carbon and zeolite improves the removal of organic contaminants.; The CPFs evaluated in this study reached efficiencies higher than 90% for mercury and lead removal.; The efficiencies for arsenic and phenols were higher than 50 and 79%, respectively.;